Efficacy and safety of mixed oriental herbal medicines for treating human obesity: a systematic review of randomized clinical trials - Park, Jung-Hyun; Lee, Myeong-Jong; Song, Mi-Young; Bose, Shambhunath; Shin, Byung-Cheul; Kim, Ho-Jun (Journal of medicinal food, 2012)
The objective of this systematic review was to assess the evidence from rigorous clinical trials evaluating the efficacy of mixed herbal medicine formulations used in traditional Oriental medicines for the treatment of obesity and to describe the safety and types of adverse events reported in such trials. To accomplish this, 14 databases were searched from inception to July 31, 2009. The search terms used were "obesity" or "obese" and "herb," "herbal," or "herbal medicine" without language restriction. All randomized clinical trials using mixed herbal medicines on obese or overweight subjects were considered for inclusion. Of the publications in the identified databases, 1144 results were searched and reviewed, and in total 12 studies were included. Their methodological quality was assessed using the Jadad score. The results of our review provide evidence suggesting that mixed Oriental herbal medicines may be safe and effective for the treatment of obesity when compared with conventional medicine, placebos, or lifestyle control. Many trials also reported improved concomitant conditions including impaired glucose tolerance, hypertension, and inflammation. Small numbers of adverse events were reported, but most were mild or not related to the intervention in itself. No significant mortality was observed in any of the trials. However, the evidence provided by the trials reviewed is not fully convincing because of their poor methodological quality. Therefore, more research and well-designed clinical trials are necessary to address these issues, as well as to assess the safety of mixed Oriental herbal medicines used to treat obesity.